Emerging Technologies for the Diagnosis of Perihilar Cholangiocarcinoma - Ilyas, Sumera I; Eaton, John; Yang, Ju Dong; Chandrasekhara, Vinay; Gores, Gregory J. (Seminars in Liver Disease, 2018)
The diagnosis of malignant biliary strictures remains problematic, especially in the perihilar region and in primary sclerosing cholangitis (PSC). Conventional cytology obtained during endoscopic retrograde cholangiography (ERC)-guided brushings of biliary strictures is suboptimal due to limited sensitivity, albeit it remains the gold standard with a high specificity. Emerging technologies are being developed and validated to address this pressing unmet patient need. Such technologies include enhanced visualization of the biliary tree by cholangioscopy, intraductal ultrasound, and confocal laser endomicroscopy. Conventional cytology can be aided by employing complementary and advanced cytologic techniques such as fluorescent in situ hybridization (FISH), and this technique should be widely adapted. Interrogation of bile and serum by examining extracellular vesicle number and cargo, and exploiting next-generation sequencing and proteomic technologies, is also being explored. Examination of circulating cell-free deoxyribonucleic acid (cfDNA) for differentially methylated regions is a promising test which is being rigorously validated. The special expertise required for these analyses has to date hampered their validation and adaptation. Herein, we will review these emerging technologies to inform the reader of the progress made and encourage further studies, as well as adaptation of validated approaches.
Keywords: cell-free DNA; differentially methylated regions; FISH